KEPUASAN KONSUMEN PADA RUMAH MAKAN MODERN MUARA KAPUAS DAN RUMAH MAKAN TRADISIONAL YU SRI DI KABUPATEN SLEMAN - Larasati, Sri (Sekolah Tinggi Pariwisata AMPTA, 2012)
Restourant is one of the businesses that is considered as an endless business. It is because a restaurant fulfills human’s need for food every day. Consequently. the more population live in the area, the higher demand of food. It couses the development of restaurant industry inYogyakarta is more rapid. The study is conducted with the purpose to know the consumer satisfaction level of Muara Kapuas restaurant and Yu Sri restaurant and to test the satisfaction differences perceived by the consumers between Muara Kapuas restaurant and YU Sri restaurant. The resulf of the study shows thst consumers are satisfied by the services provided by Muara Kapuas. The costumers Satisfaction in sequence start from the biggest the srevice quality, amenity quality, accessbility quality and product quality. The consumers are satisfied on the YU Sri restaurant service. The costumer satisfaction of Yu Sri restaurant in sequence start from the biggest is product quality, service quality, amenity quality and accessibility quality. The analysis result of the costumers satisfaction differences is found between Muara Kapuas is restaurant and YU Sri restaurant. In the services quality aspect, amenity quality and accessibility quaity, the satisfaction level of that of the Muara Kapuas restaurant is higher than the the costumers of YU Sri restaurant. While inthe product quality aspect, The Yu Sri restaurant consumers have satisfaction level than that of the Muara Kapuas Restaurant consumers. Keywords : Product Quality, Service Quality, Amenity Quality, Accessibility Quality.